The huge bag of worries (London Hodder Children's Books, 1996)
Wherever Jenny goes, her worries follow her - in a big blue bag. They are there when she goes swimming, when she is watching TV, and even when she is in the lavatory. Jenny decides they will have to go. But who can help her? BIG BOOKS encourage shared reading and collaborative learning. Allow teachers and parents to encourage discussion and they are ideal for class and group work. Ages5+.
Keywords: Worry -- Pictorial works -- Juvenile fiction -- Children's stories -- Pictorial works -- Big books